Properties of Interacting Low-Dimensional Systems. - Gumbs, Godfrey (Wiley, 2013)
Filling the gap for comprehensive coverage of the realistic fundamentals and approaches needed to perform cutting-edge research on mesoscopic systems, this textbook allows advanced students to acquire and use the skills at a highly technical, research-qualifying level. Starting with a brief refresher to get all readers on an equal footing, the text moves on to a broad selection of advanced topics, backed by problems with solutions for use in classrooms as well as for self-study. Written by authors with research and teaching backgrounds from eminent institutions and based on a tried-and.